2012
DOI: 10.1063/1.4729327
|View full text |Cite
|
Sign up to set email alerts
|

Convective cell generation by kinetic Alfvén wave turbulence in the auroral ionosphere

Abstract: Modulation of convective cells by kinetic Alfvén wave (KAW) turbulence is investigated. The interaction is governed by a nonlinear dispersion relation for the convective cells. It is shown that KAW turbulence is disrupted by excitation of the large-scale convective motion through a resonant instability. Application of the results to the auroral ionosphere shows that cross-scale coupling of the KAW turbulence and convective cells plays an important role in the evolution of ionospheric plasma turbulence. V C 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Very recent papers (e.g. Rudakov et al 2011;Kumar and Sharma 2011;Zhao et al 2011Zhao et al , 2012Das et al 2012;Kumar 2012) confirm the increasing interest in such phenomena. Zhao et al (2011) thus considered the interaction between three Alfven waves, where one wave propagates along the external magnetic field whereas the other two waves have oblique propagation directions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Very recent papers (e.g. Rudakov et al 2011;Kumar and Sharma 2011;Zhao et al 2011Zhao et al , 2012Das et al 2012;Kumar 2012) confirm the increasing interest in such phenomena. Zhao et al (2011) thus considered the interaction between three Alfven waves, where one wave propagates along the external magnetic field whereas the other two waves have oblique propagation directions.…”
Section: Introductionmentioning
confidence: 90%
“…Zhao et al (2011) thus considered the interaction between three Alfven waves, where one wave propagates along the external magnetic field whereas the other two waves have oblique propagation directions. Furthermore, Zhao et al (2012) showed that such couplings lead to large-scale self-organized convective vortex and vortex chain configurations (e.g. Chmyrev et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…By combining Eqs. (8) and (12), we can derive a nonlinear equation to describe the nonlinear coupling system of the KAWs,…”
Section: The Nonlinear Equationsmentioning
confidence: 99%
“…1,2 Recently, the nonlinear properties of the KAWs have been attracting much attention. [3][4][5][6][7][8] KAWs can interact with the large-scale MHD Alfv en waves, 9,10 where the wave energy can be transferred directly from the MHD scales to the kinetic scales. KAWs can also couple with high-frequency modes, such as the ion cyclotron, lower hybrid, and Langmuir waves and be excited by the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Because the electron thermal speed exceeds the Alfvén speed, the electrons respond adiabatically to the wave fields. The nonlinear properties of KAW convey its theoretical and analytical usefulness (Zhao et al 2010(Zhao et al , 2011(Zhao et al , 2012. Highly oblique KAW are considered good candidates for the observed solar wind turbulence spectrum at scales below ion gyro-radius (Howes 2015).…”
Section: Introductionmentioning
confidence: 99%